A Reflective Approach to Optimising Pedagogical Action Research - Șova, Tatiana; Borozan, Maia (Didactica Danubiensis, 2026)
The article examines the role of reflection in enhancing pedagogical action research, emphasizing its relevance for the improvement of educational practices and the professional development of teachers. Pedagogical action research is framed as a systematic, contextualized, and participatory inquiry addressing authentic problems in educational settings, positioning the teacher in the dual role of practitioner and researcher. Pedagogical reflection is conceptualized as an ongoing cognitive and metacognitive process that enables critical engagement with teaching experience, its reinterpretation, and the evidence-informed pedagogical decision-making. The article argues that reflection, enacted as reflection-in-action, reflection-on-action, and reflection-for-action, contributes to the quality of pedagogical action research by facilitating the identification and framing of the research questions, guiding the adaptation of methodological approaches, and the in-depth interpretation of findings. By embedding pedagogical reflection throughout all phases of the research process, from identifying the problem situation to evaluating the outcomes of the intervention, the research maintains coherence between theory and practice while remaining contextually relevant. At the same time, pedagogical reflection supports the development of a reflexive culture within pedagogical action research, reinforces teachers’ professional identity, and fosters an educational process responsive to the dynamics and complexity of contemporary contexts.